Características da carcaça e da carne e perfil de ácidos graxos de cordeiros de duas raças submetidos a níveis de inclusão de casca de grão de soja na dieta - Wommer, Tatiana Pfuller (2013)
The aim of this study was to evaluate carcass and meat characteristics of lambs from two genetic groups fed diets with different inclusions of soybean hulls in replacement of forage. Forty uncastrated male lambs were used, 20 from the Texel breed and 20 from Ideal breed, weaned approximately at 60 days and housed in individual pens were randomly divided into four groups according to the level of inclusion of soybean hulls in the diet: 0%, 33.5%, 66.5% and 100% of soybean hulls in replacement of sorghum silage. Lambs were slaughtered when they reached 60% of maturity body weight, 27 kg for Ideal breed animals and 32 kg for the Texel breed animals, being determined qualitative and quantitative carcass and meat. Texel lambs had higher average daily weight gain and carcass yield (P<0,05), being higher when it raises the level of soybean hulls. The genetic group did not affect the variables related to fat deposition as marbling, greasing state and subcutaneous fat thickness. The Texel breed, presented greater morphometric measurements of carcass (P<0,05) when compared with Ideal animals. The racial group did not alter the relative weight of the carcass cuts (P>0,05), however affects the tissue composition. Shoulder was the cut that best predicts the total carcass tissue composition of Texel and Ideal lambs. The genetic group affects the protein content of the meat, being superior to the animals of the Texel. The inclusion level of soybean hulls exerts influence on the moisture content of lamb meat. The race affected the pH, temperature, color, odor and cooking losses from lamb meat (P<0,05). The highest levels of soybean hulls result in changes in the texture profile, in lighter meat, with softer flavor and terderness. The race and the level of soybean hulls not affect the cholesterol content (P<0,05). Among the identified fatty acids, only conjugated linoleic acid had significant difference between the two breeds, being superior to the animals of the Texel breed.